40-years of relative age effects: life is not fair! - Barnsley, Roger H. (Frontiers in Sports and Active Living, 2025)
This paper explores the Relative Age Effect (RAE) after nearly 40 years since its initial examination in sports. Two original studies identified significant participation differences between relatively older and younger players in age-grouped elite hockey and soccer. In the current study, we replicate the original analyses using 2023 data. By comparing data from the original studies and 2023, focusing on Major Junior A hockey in North America and the Under-17 and Under-20 World Soccer Tournaments, we observe remarkably similar RAE patterns. For instance, both the original and the 2023 studies indicate that about 40% of elite young adult players were born in the first quarter of the age cohort, compared to just 10% in the last quarter. This paper underscores the ongoing advantages and disadvantages created by RAE and calls for greater focus on strategies to mitigate its unfair effects in sports and education.